Higher education in Libya: Challenges and future plans (in Arabic language) - Mustafa M. El-Fakhri; Salma A. Bukhatwa (Libyan International Medical University Journal)
Educational institutions are the principle pillars for establishment of sustainable human development which leads to community progress. Therefore, it is essentially important to develop their infrastructure, programs, and financial resources and assure the quality of their outcome to effectively respond and fulfill community needs. With current unprecedented scientific advancement in all aspects of life, it is becoming a formidable task to stay internationally competent. Continuous development and improving educational programs are therefore a must. The future requirements of education are choosing quality over quantity and adopting modern, reliable teaching methods in order to acquire knowledge, develop skills and attitudes that comply with good professional practice to meet the challenge of globalization. Education in Libya is free for everyone from elementary school up to university level but the general decline in the quality of Libyan higher educational system within the last four decades is well recognized. The efficiency of its product has been proven to be inconsistent with the national economical and developmental needs. Internal challenges of the higher educational system in Libya that affecting its own performance are presented in this paper, even though this does not under estimate the effect of other external threats, but they just remain beyond the scope of this paper. These challenges include; lack of a national strategic plan, poor primary and secondary school output, excessive students' admission, structural problems, poor infrastructure, administrative and legal problems, poor academic staff performance, outdated curricula and teaching methods, poor financial resources, poor research and postgraduate programs. Inevitably, the first step in treatment of such situation is to adopt a national strategy for higher education to know where we stand and to decide where to go and how to reach there. This of course in addition to linking educational programs to local, national and international market needs and promoting investment in education.